DIAGNOSIS VISUAL MASALAH UNSUR HARA ESENSIAL PADA BERBAGAI JENIS TANAMAN - Devi Armita; Wahdaniyah Wahdaniyah; Hafsan Hafsan; Hafizhah Al Amanah (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2022)
Essential nutrients are chemical elements needed by plants to support their growth and development. Essential nutrients based on the level of plant needs are divided into three, namely basic nutrients, macronutrients and micronutrients. Plants have the potential to experience nutrient problems, either deficiency or toxicity. Nutrient deficiency and toxicity experienced by plants can be identified by performing a visual diagnosis which is the easiest method to apply. This study aims to identify nutrient problems experienced by various types of plants based on visual symptoms shown by plants. This research was conducted in November 2021 in the vicinity of the researcher's residence. This research is an exploratory descriptive study conducted by observing various types of plants suspected of having nutrient deficiency and toxicity problems which are then compared with related references (books and journals). The results showed that there were 10 plant species that showed symptoms of deficiency or toxicity of macronutrients and micronutrients based on visual symptoms, namely rambutan, mung beans, gude beans, corn, cassava, bananas, onion, hibiscus, elephant ears, and taro. Keywords: deficiency; macronutrient, micronutrient; plant; toxicity; visual diagnosis